FERMI LARGE AREA TELESCOPE AND MULTI-WAVELENGTH OBSERVATIONS OF THE FLARING ACTIVITY OF PKS 1510-089 BETWEEN 2008 SEPTEMBER AND 2009 JUNE - Abdo, A. A.; Ackermann, Markus; Agudo, Ivan; Ajello, Marco; Allafort, A.; Aller, H. D.; Aller, M. F.; Antolini, E.; Arkharov, A. A.; Axelsson, Magnus; Bach, U.; Baldini, Luca; et al. (Astrophysical Journal, 2010)
We report on the multi-wavelength observations of PKS 1510-089 (a flat spectrum radio quasar (FSRQ) at z = 0.361) during its high activity period between 2008 September and 2009 June. During this 11 month period, the source was characterized by a complex variability at optical, UV, and gamma-ray bands, on timescales down to 6-12 hr. The brightest gamma-ray isotropic luminosity, recorded on 2009 March 26, was similar or equal to 2 x 1048 erg s-1. The spectrum in the Fermi Large Area Telescope energy range shows a mild curvature described well by a log-parabolic law, and can be understood as due to the Klein-Nishina effect. The. -ray flux has a complex correlation with the other wavelengths. There is no correlation at all with the X-ray band, a weak correlation with the UV, and a significant correlation with the optical flux. The. -ray flux seems to lead the optical one by about 13 days. From the UV photometry, we estimated a black hole mass of similar or equal to 5.4 x 10(8)M(circle dot) and an accretion rate of similar or equal to 0.5M(circle dot) yr(-1). Although the power in the thermal and non-thermal outputs is smaller compared to the very luminous and distant FSRQs, PKS 1510-089 exhibits a quite large Compton dominance and a prominent big blue bump (BBB) as observed in the most powerful gamma-ray quasars. The BBB was still prominent during the historical maximum optical state in 2009 May, but the optical/ UV spectral index was softer than in the quiescent state. This seems to indicate that the BBB was not completely dominated by the synchrotron emission during the highest optical state. We model the broadband spectrum assuming a leptonic scenario in which the inverse Compton emission is dominated by the scattering of soft photons produced externally to the jet. The resulting model-dependent jet energetic content is compatible with a scenario in which the jet is powered by the accretion disk, with a total efficiency within the Kerr black hole limit.
CRIS-Team WoS Importer:2020-01-15